Function and Form in Territorial Planning: The Case of Lens in the Mining Basin in Nord and Pas-de-Calais – France - Policarpo, Mauricio Aquilante; Souza, Rita de Cassia Martins de (Sociedade & Natureza, 2024)
This article purposes to engage in a discussion regarding the transformations and restructuring of the city of Lens, located in the department of Pas-de-Calais, in the administrative region of Hauts-de-France, northern France. This discussion pertains to the spatial transformations of the categories of form and function during the evolution of industrial capitalism and, subsequently, globalization. The process of "Territorial Reconversion" implemented in the area, through state planning, from the 1960s to 1990 (the year of the closure of the last coal mine), aimed to alter the region’s specialization in response to the serious issues of unemployment and economic recession. Thus, through the establishment of infrastructure and urban remodeling, the French state, in association with policies from the European Union, involving private companies and civil organizations in the region, organized itself to transform the area by changing the economic profile linked to mining and textile production to more dynamic and productive activities. These strategies influenced the transformations of the urban space of the city of Lens, reshaping it towards cultural activities (especially music and cinema workshops) and tourist activities. Among the latter, the installation of a branch of the Louvre Museum stands out. This article aims to reflect on these transformations in Lens, based on the analysis of the introduction of new forms and functions, as well as the re-signification of old forms enveloped by new functions.